2021
DOI: 10.1017/s1460396921000248
|View full text |Cite
|
Sign up to set email alerts
|

Review of novel liquid-based biomarkers for prostate cancer: towards personalised and targeted medicine

Abstract: Background: Prostate cancer is the most commonly diagnosed cancer in men and it is responsible for about 10% of all cancer mortalities in both American and Canadian men. At present, serum prostate-specific antigen levels remain the most commonly used test to detect prostate cancer, and the standard and definitive diagnosis of the disease is via prostate biopsy. Conventional tissue biopsies are usually invasive, expensive, painful, time-consuming, and unsuitable for screening and need to be consistently ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…88 Prostate-specific membrane antigen (PSMA) Prostate-specific membrane antigen (PSMA) is a type II membrane glycoprotein with several enzymatic activities and it is encoded by the PSMA (or FOLH1, folate hydrolase 1) gene located on the short arm of chromosome 11 at position 11.12 (11p11.12). 11,[96][97][98][99][100][101][102][103] According to Bouchelouche et al, 97 PSMA is expressed in secretory cells within the prostatic epithelium and is absent or moderately expressed in hyperplastic and benign tissue. Xiao et al 103 reported that, since the discovery of PSMA, a variety of techniques such as tissue immunohistochemistry, reverse transcription PCR, in situ hybridisation and Western blot analysis have been used to demonstrate that it is expressed predominantly in prostate tissue, thus it is downregulated in BPH, but overexpressed in primary, metastatic prostate carcinoma and in patients with recurrences after androgen deprivation therapy.…”
Section: Osteopontin (Opn)mentioning
confidence: 99%
See 3 more Smart Citations
“…88 Prostate-specific membrane antigen (PSMA) Prostate-specific membrane antigen (PSMA) is a type II membrane glycoprotein with several enzymatic activities and it is encoded by the PSMA (or FOLH1, folate hydrolase 1) gene located on the short arm of chromosome 11 at position 11.12 (11p11.12). 11,[96][97][98][99][100][101][102][103] According to Bouchelouche et al, 97 PSMA is expressed in secretory cells within the prostatic epithelium and is absent or moderately expressed in hyperplastic and benign tissue. Xiao et al 103 reported that, since the discovery of PSMA, a variety of techniques such as tissue immunohistochemistry, reverse transcription PCR, in situ hybridisation and Western blot analysis have been used to demonstrate that it is expressed predominantly in prostate tissue, thus it is downregulated in BPH, but overexpressed in primary, metastatic prostate carcinoma and in patients with recurrences after androgen deprivation therapy.…”
Section: Osteopontin (Opn)mentioning
confidence: 99%
“…At present, serum PSA level is the most commonly used test for the detection of prostate cancer, although these levels can also be elevated in benign conditions, have limited specificity and result in high rates of overdiagnosis and treatment of a significant number of indolent disease. 5,[7][8][9][10][11] According to Hessels et al, 12 PSA-based opportunistic screening has led to an increase in prostate cancer overdiagnosis and overtreatment due to the high incidence of clinically insignificant disease. Therefore, in order to shift the treatment paradigm of prostate cancer towards more patient-specific and targeted therapy, there is a need for a clear system that makes its detection binary so as to minimise the rate of inaccurate detections.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations